Mass Customization A Supply Chain Approach - Chandra, Charu; Kamrani, Ali K. (Springer US, 2004)
Mass Customization: A Supply Chain Approach is a text on the emerging topic of mass customization in manufacturing. The contributed chapters in this book provide a unified treatment to the topic by offering coverage in four main categories - concepts and current state of research; problem solving frameworks, models, and methodologies; supportive techniques and technologies for enabling mass customization; and future research agenda. The book blends theory and practice and includes prototypical applications to illustrate this complex, yet emerging field of inquiry